448 Prescribing of oral antibacterial drugs in primary care out-of-hours services: a scoping review. (13th April 2023) - Al Hussain, S K; Deslandes, R; Hodson, K
Abstract: Introduction: The rapid spread of antimicrobial resistance (AMR), which causes a serious threat to both human health and the global economy, is primarily linked to the overuse and misuse of antibacterial drugs. The AMR crisis is significantly impacted by the use of antibacterial drugs in primary care (1). Within these settings, oral antibacterial drugs are considered one of the most frequently prescribed group of medicines. It has been claimed that within primary care, the proportion of antibacterial drug prescribing is higher outside the regular working hours (out-of-hours (OOH) services) compared to in-hours (IH) services (2). Aim: To identify the existing body of literature around oral antibacterial drug prescribing within primary care OOH services. Methods: The scoping review was guided by the Joanna Briggs Institute manual and reported in accordance with the PRISMA-ScR. Seven electronic databases (Medline, Embase, Emcare, CINAHL, Scopus, Web of Science, and Cochrane Library) were systematically searched, and the results were screened against pre-defined eligibility criteria. Original and secondary analysis studies that addressed oral antibacterial prescribing in OOH primary care and were published in English were included. Titles and abstracts were independently screened by three reviewers. A pre-piloted extraction form was used to extract relevant data. A narrative synthesis approach was used to summarise the results. Results: The initial search yielded 834 records. Upon screening, 28 publications fulfilled the eligibility criteria. Included studies originated from nine high-income countries, with the most frequent being the United Kingdom (six studies, 21.4%) followed by Belgium (five studies, 17.9%). Literature on antibacterial prescribing in OOH services was mostly from quantitative studies (23 studies, 82.14%), with only a few employing a qualitative design (five studies, 17.86%). Different themes and sub-themes were identified across these studies. The majority discussed antibacterial prescribing data in terms of the commonly prescribed medications and/or associated conditions. Eleven studies provided a comparison between IH and OOH settings. Seven studies reported the trends of prescribing over time; of these, three explored prescribing trends before and during COVID-19. The impact of intervention implementation on prescribing was investigated in two studies, an educational intervention in one study and the use of an interactive booklet in the other study. Four studies assessed the quality/appropriateness of prescribing either by adherence to guidelines or antibiotic prescribing quality indicators . Limited studies explored prescribing predictors and patients' expectations and satisfaction with OOH services. In contrast, qualitative studies focussed more on exploring prescribers' experiences, perspectives, behaviours, and the challenges they face during consultations within OOH settings which may influence their decision-making process. Of these, one study explored why patients consult OOH services and how they communicate their problems. Conclusion: This review shows the key areas around oral antibacterial prescribing in primary care OOH services. While there is a satisfactory number of published articles covering various areas within OOH, the use of different approaches to OOH across countries may confound the comparison of practice. A strength of this work is using three reviewers to screen identified records independently. Further research is needed to provide a better understanding of current practice in these settings and how it may be contributing to AMR. References: 1. Costelloe C, Metcalfe C, Lovering A, Mant D, Hay AD. Effect of antibiotic prescribing in primary care on antimicrobial resistance in individual patients: systematic review and meta-analysis. BMJ. 2010;340:c2096. 2. Dyrkorn R, Gjelstad S, Espnes KA, Lindbæk M. Peer academic detailing on use of antibiotics in acute respiratory tract infections. A controlled study in an urban Norwegian out-of-hours service. Scand J Prim Health Care. 2016;34(2):180-5.